2013
DOI: 10.1093/carcin/bgt340
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2–Sp1 cooperation induces invasion by upregulating cadherin-11 and integrin α5 expression

Abstract: Epithelial-mesenchymal transition (EMT) is a process implicated in invasion and metastasis. EMT is characterized by repression of epithelial markers and induction of mesenchymal markers. ZEB2 is a transcriptional repressor of E-cadherin, leading to EMT. Previously, we have shown that ZEB2 directly upregulates integrin α5 transcription by cooperating with the transcription factor Sp1. In this study, we investigated the precise mechanism by which ZEB2 modulates invasion and EMT events and the role of Sp1 in ZEB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…In addition, the Gas6/Axl pathway upregulates Slug expression through MAPK [29, 51], suggesting a positive feedback loop between Slug and Axl during cancer progression. On the other hand, we previously reported that ZEB2 directly interacts/cooperates with Sp1 to function as a transcriptional activator of mesenchymal genes (vimentin, integrin α5, and cadherin-11) to induce invasion [53]. We also found that functional cooperation between Twist1 and AP-1 induces EMT and invasion [54].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the Gas6/Axl pathway upregulates Slug expression through MAPK [29, 51], suggesting a positive feedback loop between Slug and Axl during cancer progression. On the other hand, we previously reported that ZEB2 directly interacts/cooperates with Sp1 to function as a transcriptional activator of mesenchymal genes (vimentin, integrin α5, and cadherin-11) to induce invasion [53]. We also found that functional cooperation between Twist1 and AP-1 induces EMT and invasion [54].…”
Section: Discussionmentioning
confidence: 98%
“…Given the expression patterns and regulation that we observe, it is possible that ZEB2 directly controls miR-200c . Indeed, although ZEB proteins are thought to act primarily as transcriptional repressors by recruiting co-repressors, such as CtBP 32,33 or NuRD 3436 , they can also induce gene activation by recruiting co-activators such as the Specificity protein (Sp1) or Yes-associated protein (YAP1) 3739 . Finally, it remains to be determined whether Zeb1 , which is expressed at very low levels in the VZ of midbrain (present study) and regulates miR-200 family members 3,40 , may crosstalk with the Zeb2-miR-200 loop.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have investigated the regulation of cadherin-11 transcription. However, GSK-3␤ has been implicated in the suppression of cadherin-11 expression (34), whereas the transcription factors ZEB2 and SP-1 have been reported to co-operate in the up-regulation of cadherin-11 expression (35). Interestingly, AP-1 can induce the expression of ZEB2 in breast cancer cells (36), and c-JUN can bind SP-1 in epidermal growth factor-stimulated squamous-cell cancer cells (37).…”
Section: Discussionmentioning
confidence: 99%